The effect of terminal alkoxy chain on mesophase behaviour, optical property and structure of chiral liquid crystal compounds derived from (−)-menthol. Issue 14 (8th December 2017) - Luo, Cong-Cong; Jia, Ying-Gang; Song, Kun-Ming; Meng, Fan-Bao; Hu, Jian-She
ABSTRACT: Herein, we present the results of our extensive investigations on the synthesis and phase behaviour of nine novel (−)-menthol-based chiral liquid crystal compounds. They possess three phenyl rings and substituted with (−)-menthyl and varying length of n -alkoxy chains at one end. With the aim of exploring the fundamental relationships between molecular structural features and thermal properties, nine terminal n -alkoxy groups from ethoxy to n -octadecaneloxy group in even numbers have been used. A detailed characterisation of their properties was carried out. The characterisation results clearly illustrate that all the series compounds show the thermodynamically stable phases; the shorter chain homologues display only the BPI and N* phases, and the middle ones exhibit BPI, N* and SA * phases while the longer chain members show the BPI, N* and SC * phases. Besides, the BPI appeared in a narrow temperature range because of their thermodynamic disruption. Temperature range of the N* phase narrows when the length of the n -alkoxy tail increases. The reflection peak is shifted towards short wavelength region with increasing temperature due to the winding of the chiral nematic helix in the N* phase. Furthermore, their inherent reflection peak intensities of reflections were gradually weakened. Graphical Abstract: